PHOENIXVILLE, A DIGEST OF THE ORDINANCES, Parks, § 1, no. 4 (Daily Republican Print 1906) (Passed 1878). - (:unkn) unknown (General Publisher, 1878)
No person shall carry fire-arms or shoot birds or throw stones or other missiles therein.”
--
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE